Intraoperative radial nerve injury during coronary artery surgery – report of two cases - Papadopoulou, Marianna; Spengos, Konstantinos; Papapostolou, Apostolos; Tsivgoulis, Georgios; Karandreas, Nikolaos (Journal of Brachial Plexus and Peripheral Nerve Injury, 2006)
Background Peripheral nerve injury and brachial plexopathy are known, though rare complications of coronary artery surgery. The ulnar nerve is most frequently affected, whereas radial nerve lesions are much less common accounting for only 3% of such intraoperative injuries.Case presentations Two 52- and 50-year-old men underwent coronary artery surgery. On the first postoperative day they both complained of wrist drop on the left. Neurological examination revealed a paresis of the wrist and finger extensor muscles (0/5), and the brachioradialis (4/5) with hypoaesthesia on the radial aspect of the dorsum of the left hand. Both biceps and triceps reflexes were normoactive, whereas the brachioradialis reflex was diminished on the left. Muscles innervated from the median and ulnar nerve, as well as all muscles above the elbow were unaffected. Electrophysiological studies were performed 3 weeks later, when muscle power of the affected muscles had already begun to improve. Nerve conduction studies and needle electromyography revealed a partial conduction block of the radial nerve along the spiral groove, motor axonal loss distal to the site of the lesion and moderate impairment in recruitment with fibrillation potentials in radial innervated muscles below the elbow and normal findings in triceps and deltoid. Electrophysiology data pointed towards a radial nerve injury in the spiral groove. We assume external compression as the causative factor. The only apparatus attached to the patients’ left upper arm was the sternal retractor, used for dissection of the internal mammary artery. Both patients were overweight and lying on the operating table for a considerable time might have caused the compression of their left upper arm on the self retractor’s supporting column which was fixed to the table rail 5 cm above the left elbow joint, in the site where the radial nerve is directly apposed to the humerus.Conclusion Although very uncommon, external compression due to the use of a self retractor during coronary artery surgery can affect – especially in obese subjects – the radial nerve within the spiral groove leading to paresis and should therefore be included in the list of possible mechanisms of radial nerve injury.